2017
DOI: 10.1016/j.jfludis.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering generalization self-measure: Preliminary development of a self-measuring tool

Abstract: Analyses indicated that test-retest reliability was high for both groups. Discriminant validity was also achieved as the SGSM scores significantly differed between the controls and PWS two groups for stuttering and speech-anxiety. Convergent validity was confirmed by significant correlations between the SGSM and other speech-related anxiety measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…According to a study by Plexico et al [9], the emotions of AWS vary depending on the communication environment. Similarly, Alameer et al [8] presented nine different communication situations to individuals who stutter. The researchers reported that the participants' anxiety scores for speaking varied in these situations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to a study by Plexico et al [9], the emotions of AWS vary depending on the communication environment. Similarly, Alameer et al [8] presented nine different communication situations to individuals who stutter. The researchers reported that the participants' anxiety scores for speaking varied in these situations.…”
Section: Discussionmentioning
confidence: 99%
“…This grouping was performed by four different speech and language therapists (SLP) in order to avoid bias. By examining the literature on stuttering, communication situations were revised in proper forms [8,27,28]. In the final stage of the questionnaire development, an SLP specialist and faculty member checked the categorization and linguistic cohesion of the items.…”
Section: Determination Of Dercsq Communication Situationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As opposed to randomized control trials (RCTs) which control for multiple variables, evidence shows that single case studies are beneficial in situations where group study outcomes cannot be applied to each individual in real-life settings (Byiers et al, 2012). Stuttering is variable on a day-to-day basis, with severity (i.e., frequency, intensity, and duration) varying across different contexts and conversation partners (Constantino et al, 2016;Alameer et al, 2017). As a result, single case designs may be more informative to clinicians and researchers by identifying treatment outcomes for a specific client as opposed to determining a single optimal treatment for all PWS.…”
Section: Experimental Designmentioning
confidence: 99%